Stages of research and development of therapeutic approaches for Duchenne myodystrophy. Part I: the period before etiotropic approaches introduction - K. S. Kochergin-Nikitskiy; S. A. Smirnikhina; A. V. Lavrov (Нервно-мышечные болезни)
Duchenne muscular dystrophy is one of the most common inherited muscular dystrophies. The cause of this disease with an X‑linked recessive type of inheritance is mutations of the DMD gene, leading to the absence of the dystrophin protein this gene encodes or its impaired function. Loss of dystrophin leads to severe degenerative processes in patients, especially in muscle tissue, with impaired muscle function, loss of ability to move independently, respiratory failure, cardiomyopathies, etc.More than 160 years have passed since the work of Guillaume‑Benjamin‑Armand Duchenne in the 19th century. Despite the efforts of many researchers who have developed various therapeutic approaches designed to alleviate the condition of patients if not cure it, few of them have significantly changed the course of the disease. Different approaches related to specific therapy of ischemia and fibrosis in affected muscles, correction of hormonal regulation of muscle tissue growth, therapeutic methods aimed at preventing damaged myocytes from excessive accumulation of calcium ions, which enhance proteolytic processes, suppression of oxidative stress in muscles, etc. have not yet shown high effectiveness both independently and in combination with glucocorticoids. The introduction of corticosteroid drugs made it possible to slow down disease development, but the average survival still does not exceed 30–40 years and patients spend many of them in a wheelchair. At the same time, the patients’ quality of life can be additionally diminished due to the common corticosteroids’ side effects.